IMPLEMENTASI PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS XI JURUSAN TKR SMK NEGERI 2 YOGYAKARTA - Eko Nurbiyanto (Jurnal Pendidikan Vokasi Otomotif, 2019)
This research aims to increase students learning outcomes of class XI TKR 4 in the PKKR at SMK N 2 Yogyakarta through the application of the Problem Based Learning model. The types of this research are Classroom Action Research (CAR). The research data retrieval is on January 7, 2019 until February 9, 2019 at SMK N 2 Yogyakarta. The research was carried out in 2 cycles where each cycle was 2 times meeting. The research subjects were students of class XI TKR 4 on the Pemeliharaan Kelistrikan Kendaraan Ringan (PKKR) subjects in the 2018/2019 academic year with a total of 21 students. Data collection is done by test, observation, and documentation. Data processing is done quantitatively by seeing the implementation of the Problem Based Learning (PBL) model and learning outcomes in each cycle. The success criteria determined are minimum 80% of students have reached the Minimum Completion Criteria (KKM) which is a minimum value of 76.00. The results of this research showed that the application of the Problem Based Learning (PBL) model is able to increase the learning outcomes of students in class XI TKR 4 in PKKR subjects at SMK N 2 Yogyakarta. The percentage of student who achieve KKM increase to 66.67% in the first cycle and 85.71% in the second cycle.